2009
DOI: 10.1159/000235801
|View full text |Cite
|
Sign up to set email alerts
|

Blind Verification of Elevated Platelet Autoantibodies in Serum of Schizophrenic Patients – Part I: Young Subjects

Abstract: Background: It has been hypothesized that the etiology of schizophrenia, in a distinct group of patients, originates from an autoimmune reaction against platelets. Previous open screenings have recorded significantly higher blood titers of platelet-associated autoantibodies (PAA) in schizophrenic patients as compared to normal healthy subjects. In addition, young schizophrenic patients at the early stages of their disorder displayed higher PAA titers than older patients with a longer duration of the disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 63 publications
1
13
3
Order By: Relevance
“…It has been previously reported that the serum of schizophrenia patients is enriched with PAA [4,6,10,11] and an inverse correlation has been detected between the duration of disease and the level of PAA titers [10,11,16]. The main objective of the present study was to assess the impact of clozapine and nonclozapine antipsychotics on PAA levels in COS patients and to evaluate a possible relationship between clinical improvement and alterations in PAA levels.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It has been previously reported that the serum of schizophrenia patients is enriched with PAA [4,6,10,11] and an inverse correlation has been detected between the duration of disease and the level of PAA titers [10,11,16]. The main objective of the present study was to assess the impact of clozapine and nonclozapine antipsychotics on PAA levels in COS patients and to evaluate a possible relationship between clinical improvement and alterations in PAA levels.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of high PAA titers may have indicated an active autoimmune process associated with the pathophysiology of COS, and it was suggested that a PAA-positive status may serve as an immune biomarker of COS [16]. We have previously observed [5,8,10] that the PAA levels in adolescent and adult schizophrenia patients were not influenced by treatment with any of the antipsychotic medications, except clozapine. Similarly, in the present study it was clearly demonstrated that there was no correlation between changes in PAA status and the clinical improvement following antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated significantly higher blood titers of PAA in adult schizophrenia patients as compared to normal healthy subjects [4,5,6]. In addition, young schizophrenia patients at their early stages of the disorder displayed higher PAA titers than older patients with longer duration of the disorder [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%